Pengaruh Kompetensi, Akuntabilitas dan Independensi pada Kualitas Audit dengan Etika Auditor Sebagai Variabel Moderasi - Wardhani, Anak Agung Istri Tirtamas Wisnu; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 23 No 1 (2018), 2018)
An auditor in performing his duties is required to produce a good quality audit. A good audit quality can be generated if an auditor is able to pay attention to the factors that influence it. Competence, accountability, independence and auditor ethics are some factors that may affect audit quality. This study aims to obtain empirical evidence of the auditor's ethical ability to strength ened the influence of competence, accountability, and independence on audit quality. The location of this research was conducted at Public Accounting Firm in Bali Province with total sample of 66 auditors. The sample was chosen using purposive sampling technique. Data collection in this research using survey method with questionnaire technique. Data analysis technique used is Moderated Regression Analysis (MRA). The results of this study show the results of testing instruments and classical assumptions are met. Based on the analysis conducted, the auditor ethics strengthen ed the relationship of competence and accountability. But on the other hand the ethics of the auditor does not affect the relationship between independence on audit quality. This can be because an auditor is experiencing a conflict of interest where an auditor feels worried about losing his client. Keywords: Competence, accountability, independence, ethical auditor, audit quality.